Physicochemical characterization of aqueous micellar systems formed by environmentally friendly salts - Cordisco, Estefanía (2015)
In this work, environmentally friendly aqueous micellar two-phase systems containing nonionic surfactants (Triton X-114, Triton X-100 and Genapol X080) and organic salts (sodium citrate and sodium tartrate) were characterized. In order to accomplish this objective, the binodal diagrams (cloud point vs. surfactant concentration) were obtained for each condition. Additionally, critical micelle concentration (CMC) and micellar hydrodynamic diameter (DH) were determined for each system. According to the obtained results, it was found that the presence of salts lowered the CMC (ΔCMC up to 0.15 mM) and cloud point values (ΔCP up to 18 °C) following the sequence: sodium citrate > sodium tartrate. In addition, the hydrodynamic diameters of the micelles were notoriously increased in presence of the studied salts, showing the high sensitivity of the described aqueous micellar two-phase systems to the medium condition. These results open perspectives for the use of greener aqueous micellar two-phase systems for bioseparation purposes.